PROBLEMA MOTIVELOR INVESTIGAŢIONALE PRIVIND STUCTURA ACTIVITĂŢII EDUCAŢIONALE ÎN CONTEXTUL ÎNVĂŢĂMÂNTULUI UNIVERSITAR - USM ADMIN (Moldova State University, 2007)
Motivation is one of fundamental problems of psychology, educational psychology, sciences of education, and didactics. The complexity and the multidimensions of motivation determine the spectrum of educational approaches, methods and techniques of its formation and it is the development thereof; the problem of investigation belongs to a completely different area especially in what regards psychology and didactics. The attitude towards investigational goals, acknowledged at the level of social needs makes the investigational activity not just useful, but even attractive in a certain context. A certain mounting, if it is stable and occupies a certain place in the student's personality, offers the required strength in overcoming the difficulties, in showing patience and perseverance. If investigational activity mounting will not be consolidated by other motivational factors, it won't have material effect. For example if the student doesn't show interest towards investigational activity, but realizes that without the knowledge offered by this activity, he/she will not advance professionally and that is why he/she makes efforts to do that particular investigational activity.